CONSTRAINTS ON MANTLE MELTING AND COMPOSITION AND NATURE OF SLAB COMPONENTS IN VOLCANIC ARCS FROM VOLATILES (H2O, S, CL, F) AND TRACE ELEMENTS IN MELT INCLUSIONS FROM THE KAMCHATKA - Portnyagin M.; Hoernle K.; Plechov P.Y.; Mironov N.; Khubunaya S. (My University, 2007)
New and published data on the composition of melt inclusions in olivine (Fo73_yi) from volcanoes of the Kamchatka and northern Kurile Arc are used 1) to evaluate the combined systematics of volatiles (H2O, S, Cl, F) and incompatible trace elements in their parental magmas and mantle sources, 2) to constrain thermal conditions of mantle melting, and 3) to estimate the composition of slab-derived components. We demonstrate that typical Kamchatkan arc-type magmas originate through 5-14% melting of sources similar or slightly more depleted in HFSE (with up to -1 wt.% previous melt extraction) compared to MORB-source mantle, but strongly enriched in H2O,B, Be, Li, Cl. F, LILE, LREE, Th and U. Mean H2O in parental melts f 1.8-2.6 wt.%) decreases with increasing depth to the subducting slab and correlates negatively with both 'fluid-immobile* (e.g. Ti, Na, LREE) and most 'fluid-mobile' (e.g. LILE, S, Cl, F) incompatible elements, implying that solubility in hydrous fluids or amount of water does not directly control the abundance of 'fluid-mobile' incompatible elements. Strong correlation is observed between H2O/Ce and B/Zr (or B/LREE) ratios. Both, calculated H2O in mantle sources (0.1-0.4%) and degrees of melting (5-14%) decrease with increasing depth to the slab indicating that the ultimate source of water in the sub-arc mantle is the subducting oceanic plate and that water flux (together with mantle temperature) governs theextent of mantle melting beneath Kamchatka. A parameterized hydrous melting model [Katzetal. 2003, G3,4(9), 1073] is utilized to estimate that mantle melting beneath Kamchatka occurs at or below the dry peridotite solidus (1245-1330 °C at 1.5-2.0 GPa). Relatively high mantle temperatures (yet lower than beneath back-arc basins and ocean ridges) suggest substantial corner flow driven mantle upwelling beneath Kamchatka in agreement with numerical models implying non-isoviscous mantle wedge rheology. Data from Kamchatka, Mexico and Central America indicate that <5% melting would lake place beneath continental arcs without water flux from the subducting slab. A broad negative correlation appears to exist between crustal thickness and the temperature of magma generation beneath volcanic arcs with larger amounts of decompression melting occurring beneath thinner arc crust (Uihosphere). In agreement with the high mantle temperatures, we observe a systematic change in the composition of slab components with increasing slab depth from solute-poor hydrous fluid beneath the volcanic front to solute-rich hydrous melt or supercritical liquid at deeper depths beneath the rear arc. The solute-rich slab component dominates the budget of LILE, LREE,Th and U in the magmas and originates through wet-melting of subducted sediments and/or altered oceanic crust at > 120 km depth. Melting of the upper parts of subducting plates under water flux from deeper luhosphere (e.g. serpentinites), combined with high .emperatures in the mantie wedge, may be a more common process beneath volcanic arcs than has been previously recognized. 0 2006 Klsevier B.V. All rights reserved.
Keywords: 38.33.15 Геохимия отдельных элементов; 38.33.17 Геохимия природных процессов; 38.35.19 Включения в минералах; 38.37.25 Вулканология; Чикурачки; Карымский; Ксудач; Плоский Толбачик; Ключевской